Financial Management Behavior: the Influence of Financial Knowledge, Financial Attitude, and Financial Literacy Mediated by Locus of Control - Damayanti, Dika; Tubastuvi, Naelati; Purwidianti, Wida; Aryoko, Yudhistira Pradhipta (Indonesian Journal of Business Analytics, 2023)
The purpose of this study is to identify the effect financial knowledge, financial attitude and financial literacy towards financial management behavior mediated by locus of control. This research used SmartPLS statistical analysis tool version 3.0. Based on the findings of this research, it shows that financial knowledge and financial literacy do not affect the locus of control, financial attitude has a positive and significant effect on the locus of control. Financial knowledge, financial literacy, and locus of control have a positive and significant effect on financial management behavior, financial attitude does not affect financial management behavior. The locus of control cannot mediate the effect of financial knowledge and financial literacy on financial management behavior, and the locus of control can mediate positively and significantly the influence of financial attitudes on financial management behavior. The implication for universities in forming good financial management behavior is to increase financial knowledge, financial literacy and locus of control, then form financial management behavior by improving financial attitude through locus of control by holding training programs, courses, seminars, or other activities from universities and faculties.